Gold catalysis: one-pot alkylideneoxazoline synthesis/alder-ene reaction - Hashmi, A. Stephen K.; Littmann, Anna Christina (Chemistry, 2012)
Based on the gold-catalyzed synthesis of methyleneoxazolines, a one-pot combination with an Alder-ene reaction was developed. For azodicarboxylates, good to very good yields (51-99 %) of the oxazolemethylhydrazinedicarboxylates were achieved with 3 mol % of the Gagosz catalyst, [Ph3PAuNTf3]. In a less-selective reaction, 4-phenyl-3H-1,2,4-triazol-3,5(4 H)-dione gave lower yields (41-49 %) of the corresponding oxazolemethylphenyltriazolidinediones. Overall, five new bonds were formed. Tetracyanoethylene afforded a cyclobutane derivative through a [2+2] cycloaddition reaction at −40 °C, but only 45 % of the spiro compound was obtained. The less-readily available KITPHOS ligands on gold gave even higher yields at lower catalyst loadings (2 mol %), but longer reaction times were required.